Bioinformatics workflow and assessment of software to seek secondary metabolites in bacteria (2017)
"The potential to discover new Natural Products (NPs) from bacteria has evolved from an in-vitro test approach to a combination of in-vitro and in-silico processes. In particular, the exploration of novel species of microbes that have not previously been studied could signify an important pool of new de novo molecules. As the potential to find new products can be studied using new software tools, this project aims to define a pipeline that can help researchers foresee the potential that bacteria have to produce NPs." -- Tomado del Formato de Documento de Grado.